A Review of Recent Advances in Red-Clay Environmental Magnetism and Paleoclimate History on the Chinese Loess Plateau - Nie, Junsheng; Song, Yougui; King, John W. (Frontiers in Earth Science, 2016)
The red-clay sequence on the Chinese Loess Plateau (CLP) was deposited during the late Miocene-Pliocene and is encoded with important information of past climate changes. However, it has received much less study in comparison to the overlying Pleistocene loess-paleosol sequence. In this paper, we review recent progress in characterizing the environmental magnetic parameter-based paleoclimate history recorded by the red-clay sequence. Several key conclusions are as follows. (1) the red-clay and the loess-paleosol sequences have similar magnetic enhancement mechanisms but magnetic minerals in the red-clay sequence have experienced a higher degree of oxidation than in the loess-paleosol sequence. (2) The CLP experienced a cooling and wetting trend from 4.5 to 2.7 Ma, caused by ice sheet expansion and East Asian summer monsoon intensification, respectively. (3) The above conclusions benefit from backfield remanence curve unmixing and comparison of magnetic grain size/concentration records, which are particularly useful in separating the temperature from the precipitation signal. A clear need in future studies is to explore the concentration and the grain size variations of hematite and goethite in the red-clay sequence and their formation mechanisms. The payback would be a clear understanding of climate history during the late Miocene-Pliocene, a possible analog for future warmer climate.